Quantitative Structural Relationship and Estimated Biological and Physicochemical Properties of Paraffin-Base Petroleum (C1-C40) - Kheradm, Khojasteh (Asian Journal of Chemistry, 2010)
The hydrocarbon compounds in petroleum have different structures. Some of them are linear and normal. This homologues series sometimes has attracted the notice for chemical and biochemical studies. The structural parameters are the useful indices for examination of structure-property relationship. Graph theory is an interesting ground for the exploration of proof techniques in discrete mathematics and its results have applications in many areas of sciences. Topological indices are the numerical value associated with chemical constitution purporting for correlation of chemical structure with various physical properties, chemical reactivity or biological activity. This study represented the quantitative structural relationship (QSR) between the number of carbon atoms in the structures of normal hydrocarbon C1-C40, logarithm of calculated octanol-water partitioning coefficients and total biodegradation [log Kow and TBd (mol/h), respectively], median lethal concentration 50 (LC50), water solubility (Sw, mg L-1/25 ºC) and some of the other calculated chemical and biochemical data in the normal hydrocarbon C1-C40 (1-40). The results would be extended for some of the other members of these compounds. The interesting results of concerning among log Kow, LC50, Sw, TBd (g/h) and some of the other data with the descriptors for this compounds are presented and discussed.